Prognostic Implications of Relations of Left Ventricular Systolic Dysfunction with Body Composition and Myocardial Energy Expenditure: The Strong Heart Study - Palmieri, Vittorio (J Am Soc Echocardiogr, 2007)
OBJECTIVE: We sought to investigate prognostic implications of the relationships of estimated left ventricular (LV) myocardial energy expenditure (MEE) with LV systolic dysfunction, body composition, and inflammation in a population-based sample of adults without overt congestive heart failure. METHODS: Echocardiography was used to assess LV ejection fraction (EF) and MEE. Body composition was evaluated by bioelectric impedance. Dietary recall was used to assess 24-hour calorie intake. Participants in the Strong Heart Study without prior congestive heart failure and with all needed data available (n = 3087) were divided based on LV EF (>55%, 54%–45%, or <45%). RESULTS: Participants with EF less than 45% were older and they had lower body mass index, adipose mass, fat-free mass, and 24-hour calorie intake than participants with normal EF (≥55%), and had greatest reductions of body mass index and physical activity in a time interval of 3.5 years, on average, elapsed between an initial clinical assessment and the evaluation at the time of the echocardiographic examination (P < .01). Lower EF was associated with male sex, hypertension, diabetes, coronary heart disease, and higher fibrinogen, C-reactive protein, and plasma creatinine levels (all P < .01). MEE was higher with lower EF (all P < .001). In Cox regression models, during approximately 8 years of observation, MEE comprised between 97 and 123 cal/min and MEE greater than 123 cal/min were associated with 2.5-fold and additional 3.3-fold higher rates of cardiac death, respectively, compared with MEE less than 97 cal/min, independently of EF, body composition, and other covariates. However, lower adipose mass predicted increased risk of cardiac death independent of MEE and EF. CONCLUSION: In a population-based sample of adults including ambulatory individuals with depressed LV systolic function but without overt congestive heart failure, depressed EF was associated independently with higher MEE, lower adipose mass, and higher fibrinogen. However, increased MEE and lower adipose mass predicted cardiac death independently of EF and other covariates.